Pre-post-racial America : spiritual stories from the front lines - Jha, Sandhya R. (St. Louis : Chalice Press, 2015)
Those people. Their issues. The day's news and the ways we treat each other, overtly or subliminally, prove we are not yet living in post-racial America. It's hard to talk about race in America without everyone very quickly becoming defensive and shutting down. What makes talking race even harder is that so few of us actually know each other in the fullness of our stories. A recent Reuters poll found 40% of White people have no friends of other races, and 25% of people of color only have friends of the same race. Sandhya Rani Jha addresses the hot topic in a way that is grounded in real people's stories and that offers solid biblical grounding for thinking about race relations in America, reminding us that God calls us to build Beloved Community. Discussion questions at the end of each chapter provide starting points for reading groups.
Cover; Title; Copyright; Contents; Introduction: Complicating the Narrative-Stories of Living Race in America; 1 The Civil Rights Movement Fifty Years Later; 2 Border Battles; 3 Murky Terminology; 4 (The Myth of) The Angry Black Man; 5 Perpetually Liminal; 6 Isn't It Really about Class?; 7 Race and Religion Post 9/11; 8 We Are Each Others' Victims Siblings; 9 Navigating Privilege; 10 #Every28hours; 11 "But I Don't Think of You As..."; 12 Oppression Olympics, Intersectional Faith, and the Integrated Self; Conclusion: Beloved Communities
Includes bibliographical references and index.
Print version record.
Keywords: United States -- Church history -- 20th century; United States -- Church history -- 21st century; Race relations -- Religious aspects -- Christianity -- History -- 20th century; United States -- Race relations; SOCIAL SCIENCE / Discrimination & Race Relations; Race relations; Race relations -- Religious aspects -- Christianity; United States; Race relations--Religious aspects--Christianity--History--20th century; United States--Church history--20th century; United States--Church history--21st century; United States--Race relations; 1900 - 2099; Electronic books; Church history; History; Electronic books